Роль закладів культури у формуванні духовно–моральних цінностей молоді - Вєлієва, Б.Т. (Культура народов Причерноморья, 2013)
У статті розглядається роль установ культури у формуванні духовно–моральних цінностей
молоді, яка визначається тим, що зміни, які сталися за останнє десятиліття в економічній, політичній,
культурній сферах, найбезпосереднішим чином позначилися на їхній свідомості. В статье рассматривается роль учреждений культуры в формировании духовно–
нравственных ценностей молодежи, которая определяется тем, что перемены, происшедшие за
последнее десятилетие в экономической, политической, культурной сферах, самым непосредственным
образом сказались на их сознании. The article deals with the urgency of forming the spiritual values of young people by means of the
enlightenment activity. The article reflects the relevance of the formation of spiritual and moral values of young
people, which is determined by the fact that the changes that have occurred over the last decade in the economic,
political and cultural spheres, the most directly have affected the minds of virtually all social groups and strata
of society. Radical changes have taken place, especially in the spiritual and moral development of the young
people who are different in many ways from their former peers. In their life they have been guided by the
imperatives that are different from those that are determined the motivation of the behavior not of the one
generation.The essence of spirituality in the context of historical knowledge is not uniquely determined. Spirituality is the
totality of all phenomena of the spirit, which includes not only the field of mental but also all that goes beyond
the psyche as the properties of the highly organized matter. Spirituality is a concept derived from the other
concept – "spirit." One of the definitions of the term "spirit" – psychic abilities, the consciousness, a thinking.
Finally, the "spirit" stands as a symbol of ethereal, supernatural beings taking part in the life of the nature or
man, and "breathing".
Traditionally, spirituality includes three principles: cognitive, moral and aesthetic. These principles correspond
to the three spheres of human activity, three spheres of spiritual values – truth, goodness and beauty. Exactly
these three principles form the criterion of the level of a human development, which is defined as a spiritual
person.
The article describe the methods, forms and means of enlightenment activity for the successful formation of the
spiritual values of young people.